Child Allergic Symptoms and Well-Being at School: Findings from ALSPAC, a UK Cohort Study. - Alison Teyhan; Bruna Galobardes; John Henderson (PLoS ONE)
Background Eczema and asthma are common conditions in childhood that can influence children's mental health. Despite this, little is known about how these conditions affect the well-being of children in school. This study examines whether symptoms of eczema or asthma are associated with poorer social and mental well-being in school as reported by children and their teachers at age 8 years. Methods Participants were from the Avon Longitudinal Study of Parents and Children. Measures of child well-being in school were child-reported (n = 6626) and teacher reported (n = 4366): children reported on their enjoyment of school and relationships with peers via a self-complete questionnaire; teachers reported child mental well-being using the Strengths and Difficulties Questionnaire [binary outcomes were high 'internalizing' (anxious/depressive) and 'externalizing' (oppositional/hyperactive) problems (high was >90th percentile)]. Child rash and wheeze status were maternally reported and symptoms categorised as: 'none'; 'early onset transient' (infancy/preschool only); 'persistent' (infancy/preschool and at school age); and 'late onset' (school age only). Results Children with persistent (OR 1.29, 95% CI 1.02 to 1.63) and late onset (OR 1.48, 95% CI 1.02 to 2.14) rash were more likely to report being bullied, and children with persistent wheeze to feel left out (OR 1.42, 95% CI 1.10 to 1.84). Late onset rash was associated with high teacher-reported internalising behaviours (OR 1.61, 95% CI 1.02 to 2.54), and persistent rash with high externalising behaviours (OR 1.37, 95% CI 1.02 to 1.84). Child sleep and maternal mental health explained some of the associations with teacher-reported mental well-being. Conclusion Symptoms of eczema or asthma can adversely affect a child's social and mental well-being at primary school. This suggests interventions, such as additional support or education of peers, should begin at early stages in schooling.